2021
DOI: 10.1152/jn.00155.2021
|View full text |Cite
|
Sign up to set email alerts
|

Tempo-spatial integration of nociceptive stimuli assessed via the nociceptive withdrawal reflex in healthy humans

Abstract: Spatial information of nociceptive stimuli applied in the skin of healthy humans is integrated in the spinal cord to determine the appropriate withdrawal reflex response. Double-simultaneous stimulus applied in different skin sites are integrated, eliciting a larger reflex response. The temporal characteristics of the stimuli also modulate the reflex e.g. by temporal summation. The primary aim of this study was to investigate how the combined tempo-spatial aspects of two stimuli are integrated in the nocicepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Since the integration of electrical stimuli at the peripheral and central level exploits both temporal and spatial cues (Henrich et al 2021 ; Mørch et al 2010 ), one might speculate that since dynamic patterns convey additional temporal information (compared to a static stimulus), the discrimination and localization of the stimulus are to be improved. Already in 1990, it was reported that our ability to detect changes in intensity is enhanced when there is a changing stimulus over a stable background (Gescheider et al 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the integration of electrical stimuli at the peripheral and central level exploits both temporal and spatial cues (Henrich et al 2021 ; Mørch et al 2010 ), one might speculate that since dynamic patterns convey additional temporal information (compared to a static stimulus), the discrimination and localization of the stimulus are to be improved. Already in 1990, it was reported that our ability to detect changes in intensity is enhanced when there is a changing stimulus over a stable background (Gescheider et al 1990 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nociceptors serve to protect the skin from noxious thermal stimuli by eliciting pain sensations. The nociceptive afferents inform the brain of potentially hazardous objects and initiate protective motor actions by quickly retracting the hand from the heat source, a behavior known as the withdrawal reflex ( Henrich et al, 2021 ), resulting from the seamless sensorimotor pathways of nociceptive temperatures ( Witney et al, 2004 ; Muniak et al, 2007 ; Sieck, 2019 ). Advanced prosthetic hands are emerging with artificial skin embedded with integrated nanosensors ( Yang et al, 2019 ; Romeo et al, 2021 ; Li et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It remains a challenge not only to warn against harmful temperatures but also take withdraw actions via reflexive, voluntary, or hybrid control. There are two modes in which voluntary action and withdrawal reflex can work together in the human hand ( Lynn et al, 2016 ; Henrich et al, 2021 ). The reinforcement control mode demonstrates the subjects’ motor intention to rush away from danger, while the contradictory mode indicates the subjects’ ability to inhibit the action of withdrawal reflex and represents that the subjects are able to tolerate this danger after careful consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Study II: "Tempo-spatial integration of nociceptive stimuli assessed via the nociceptive withdrawal reflex in healthy humans" [2] As introduced above and further discussed in the following chapters, SS seems to be a key mechanism in the encoding of pain intensity and the optimal NWR. This integration is most likely implemented within the spinal cord reflex pathway.…”
Section: Research Questions Addressed In the Thesismentioning
confidence: 99%
“…Particularly, Study I [1] suggested that simultaneous stimulation of different sites of the sole of the foot is integrated by spinal neurons. Study II [2] investigated whether the introduction of a temporal delay (inter-stimulus intervals, ISIs) between stimuli delivered in different or the same site(s) affects the integration of nociception at the spinal level. That study hypothesized that short ISIs are integrated at spinal levels and facilitate NWRs.…”
Section: Nociceptive Processing Of Temporal Characteristicsmentioning
confidence: 99%